Unmet needs for family planning and its socio-demographic correlates among women in the reproductive age group in central rural India - Pawar, Ramesh Devidas; Solanke, Shital Pratapsing (International Journal Of Community Medicine And Public Health, 2020)
Background: Unmet need is the discrepancy between reproductive intentions and birth control practices. If the unmet needs remained neglected it leads to population explosion which is one of the greatest threats to India’s economic, social and political development. A community-based study was carried out in rural areas with the objective to find the prevalence of unmet need for family planning and its socio-demographic determinants among married women of reproductive age. Methods: A community based cross sectional study was conducted between January to June 2019. After calculation of sample size 670 participants were selected by simple random sampling method. Predesign and semi structured Performa was used for data collection. Data was collected and analyse using Epi Info 7. Results: Unmet needs of family planning among the study subject was 31.19% (57.58% for the spacer and 42.42% for limiter). It was significantly higher among the Muslim (66.67%) and Boudh (40.38) religion. It was higher among Illiterate (40.82%), women residing in joint families (72.16%). Unmet need of family planning was significantly associated with age of women, religion, educational status of women and their husbands, occupation, type of family, no of children the women have and age at marriage. Conclusions: Unmet needs among married women in the reproductive age group was still high and was significantly associated with age of women, religion, educational status of women as well as their husband, occupation, type of family, number of children the women had and age at marriage.